Evolutionary economics and psychology - Ulrich Witt (Max Planck Institute of Economics, 2006)
Evolutionary economics is a paradigm for explaining the transformation of the economy. To achieve its goal, it needs being founded on a proper theory of economic behavior. The paper discusses these foundations. It is argued that the historical malleability of economic behavior is based on the interactions between innate behavior dispositions and adaptation mechanisms on the one hand and the limited, and always selective, cognitive and observational learning that contributes to an ever more extended and differentiated action knowledge. The implications of this interpretation are outlined in an exemplary fashion for the case of the evolution and growth of consumption.
Keywords: 330; Wirtschaftswissenschaft; Psychologie; Wirtschaftspsychologie; Evolutionsökonomik; Theorie